Envelhecimento ativo de professores de um programa de atividades físicas da UnATI/ESALQ/USP - Moraes, Paulo Fernando [UNESP] (2014)
Active aging is a process that focuses on the quality of life of elderly, as proposed by WHO and Brazilian official documents. There is a break with the world of work with retirement, and increased leisure time. Studies indicate adherence to physical activity at this stage, enabling active aging. Knowing that regular physical activity is associated with several health benefits and functional capacity, this study aimed to understand the active aging process of the group of individuals who participate in a physical activity program UnATI/ ESALQ-USP, especially of retired teachers, featuring the group regarding: 1- overall functional fitness index (OFFI); 2- level of physical activity; 3- quality of life (in three domains: physical functioning, role limitations due to physical health and vitality); 4- physical activity in the retirement of teachers group. Functional fitness (OFFI) was evaluated by the battery of tests AAHPERD; the level of physical activity was assessed by the IPAQ long version and the quality of life using the SF-36 questionnaire - Short Form, the results were analyzed with nonparametric statistics through U of Mann Whitney test and correlated statistically by Spearman. Also exercise classes were observed and there was realized interviews about the relationship between physical activity and retirement teachers. 160 individuals in program ESALQ of physical activity (0.4% of elderly population of Piracicaba), 47 subjects volunteered for the study, 18 teachers, who signed a consent form. We evaluated age, weight, height and BMI, with the 95%. Retired teachers represented 38% of sample when it is compared to each other professions of the other participants (N = 47). In an interview, teachers (89%) said that they did not perform physical activity before retirement, so UnATI- ESALQ program contributes to activity in elderly. Although most participants (46.94%) of the group studied was classified as weak or very weak when OFFI was...